THU0409 Post-Marketing Survey of Mizoribine for Lupus Nephritis (Mile 2010 Study Interim Analysis). (9th June 2015) - Takeuchi, T.; Okada, K.; Yoshida, H.; Yagi, N.
Abstract : Background: Mizoribine (MZR) is an immunosuppressant drug developed in Japan. MZR was first approved for the treatment of lupus nephritis (LN) in 1990. MZR's mechanism of action selectively inhibits IMP dehydrogenase, a key enzyme in purine synthesis, which leads to the suppression of lymphocyte proliferation. With the availability of new treatments for LN and widespread use of SLEDAI-2K as a standard evaluation method [1], a post-marketing survey of MZR for the treatment of LN was conducted to confirm the efficacy and safety of MZR for LN. Objectives: Efficacy and safety of MZR was evaluated over a two-year period for the treatment of LN. Methods: The observation period was two years. Efficacy was evaluated using the criteria for complete renal remission (CRR) (ACR 2006) [2], and SLE activity was evaluated using SLEDAI-2K. Renal findings were evaluated using urine protein, serum creatinine, and eGFR. Changes in concomitant steroid dose were also examined. Results: Five hundred seventy-six (576) subjects were registered from March 2010 to March 2013. From the completed questionnaires after the first year, the safety and efficacy for 443 subjects (excluding 5 subjects) were investigated for one year. The rate of subjects who continued administration was 69.8%. Adverse reactions occurred in 60 of the 443 subjects (13.5%). The main adverse reactions were 12 events (2.7%) of herpes zoster, 5 events (1.1%) of hyperuricemia, and 4 events (0.9%) of anemia. Serious adverse drug reactions were observed in 12 patients (2.7%). The CRR rate was 9.4%. SLEDAI-2K scores improved from 11.1±8.9 to 5.6±5.4 (p<0.0001). Improvement was observed in arthralgia, erythema, and renal/hematological findings. Urine protein (g/gCr) decreased from 1.5±2.5 to 0.9±2.0 (p=0.0012). Serum creatinine (mg/dL) was 0.9±0.6 at initiation and 0.8±0.6 after one year. Steroid dose was reduced from 18.5±14.6 to 10.5±7.2 mg/day (p<0.0001). Conclusions: MZR was effectively and safely used for the treatment of LN. We confirmed that MZR improved urine protein and reduced steroid dose. References: Dafna D. Gladman, Dominique Ibanez, and Murray B. Urowitz. Systemic Lupus Erythematosus Disease Activity Index 2000. Journal of Rheumatology 2002; 29(2):288-291. Renal Disease Subcommittee of the ACR Ad Hoc Committee on SLE Response Criteria. Arthritis & Rheumatism 2006;54(2):421-432. Acknowledgements: The authors wish to thank all the investigators for their contributions to the implementation of this study. Disclosure of Interest: T. Takeuchi Grant/research support from: Astellas Pharma, Bristol–Myers K.K., Chugai Pharmaceutical Co, Ltd., Daiichi Sankyo Co., Ltd., Eisai Co., Ltd., Mitsubishi Tanabe Pharma Co., Pfizer Japan Inc., Santen Pharmaceutical Co., Ltd., Takeda Pharmaceutical Co., Ltd., Teijin Pharma Ltd., AbbVie GK, Asahikasei Pharma Corp., and Taisho Toyama Pharmaceutical Co., Ltd., SymBio Pharmaceuticals Ltd., Consultant for: Astra Zeneca K.K., Eli Lilly Japan K.K., Novartis Pharma K.K., Mitsubishi Tanabe Pharma Co., and Asahi Kasei Medical K.K., abbivie GK, Daiichi Sankyo Co., Ltd., Bristol–Myers K.K., Nipponkayaku Co.Ltd., Paid instructor for: Mitsubishi Tanabe Pharma Co., Eisai Co., Ltd., Abbivie GK, Speakers bureau: AbbVie GK., Bristol–Myers K.K., Chugai Pharmaceutical Co, . Ltd., Eisai Co., Ltd., Janssen Pharmaceutical K.K., Mitsubishi Tanabe Pharma Co., Pfizer Japan Inc., and Takeda Pharmaceutical Co., Ltd., Astellas Pharma, and Diaichi Sankyo Co., Ltd., Celtrion, Nipponkayaku Co.Ltd, K. Okada: None declared, H. Yoshida: None declared, N. Yagi: None declared